PERBANDINGAN INDUK JANTAN DAN BETINA TERHADAP KEBERHASILAN DERAJAT PENETASAN DAN KELULUSAN HIDUP LARVA IKAN MAS KOKI (Carrasius auratus) - Fretty J Simbolon; Budi Utomo; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
The germination of freshwater fish has good future prospect in local andexport. One of freshwater that has a higher selling price and market demand ismuch enough in local or export is goldfish (Carracius auratus). This researchaims to get the comparison quantity of good parents for maximal spawning anddetermine the ratio of male parent and female parent of goldfish which differenton hatching and survival rate of larvae. This research method was used acompletely randomized design with 3 treatments and 3 replications. The firsttreatment was the comparison between male parent and female parent 2 : 1, thesecond treatment was the comparison between male parent and female parent 3 : 1and the last treatment was the comparison between male parent and female parent4 : 1. This research was conducted in 2015 on July until August. The result of thisresearch showed that the comparison of parents quantity has significant effect onthe degree of fertilization and showed the highest hatching rates got from the lasttreatment (82. 87 %) in comparison of male parent and female parent 4 : 1 whichthe chances of sperm to fertilize an egg was greater so that the number of eggsthat hatch will also be greater and the highest survival rate of larvae and alsoobtained from the last treatment (81. 82%).Keyword: Hatching Rate, Survival Rate, Goldfish.